IBNU TAIMIYAH'S POLITICAL THINKING (EMPLOYEE APPOINTMENT AND STATE FINANCIAL MANAGEMENT) - Zul Hilmi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Abstract Appointment of employees and management of state finances are two things that cannot be separated. Appointment of employees will not be carried out without involving financial management and financial management will not be carried out without an employee in charge of managing it. Therefore, it is not surprising that the appointment of employees and financial management are two things that cannot be separated.This study aims to find out how the appointment of employees and financial management according to the political thought of Ibn Ibn Taymiyah, who is a person who is known as a scholar and also the father of Islamic administration. This is very interesting because it is very rare for anyone to thoroughly discuss the appointment of employees and the management of state finances based on the thoughts of Ibn Taimiyah. This study uses a qualitative approach. This type of research is qualitative with descriptive analysis model. The data were collected by means of libraryresearch, where the researcher used the library as a source of data collection.The results of this study are according to Ibn Taimiyah in the appointment of employees, a ruler should not be careless and must select correctly and carefully every person who will be appointed as an employee. According to Ibn Taymiyya, state finances must be managed by the state properly and in a trustworthy manner and should not misappropriate these assets.    Keywords: Appointment of employees, Financial Management, Ibn Taimiyah